The Growth of Homeowner Property Taxes: Evidence from Wisconsin - Boldt, Rebecca; Caruth, Bradley; Reschovsky, Andrew (My University, 2009)
The authors examine how Wisconsin homeowners' property tax liabilities and burdens change over time. They find that the amount paid and the economic hardship created vary widely among homeowners. Relative to income, some homeowners face high and increasing property taxes, while others pay low and/or declining taxes.